Pelatihan Pembuatan Kelapa Menjadi Minyak Murni/Virgin Coconut Oil (VCO) di Desa Wolowiro Kecamatan Paga Kabupaten Sikka - Nur Tiara Hasanah; Reza Fauzia; Sasmita Putri Hairani; Widya Astuti (Universitas Muhammadiyah Manado, 2026)
Wolowiro Village, Paga District, Sikka Regency possesses abundant coconut resources; however, their utilization remains limited and has not yet generated optimal economic value for the local community. This community service program aimed to improve community knowledge and skills in processing coconuts into Virgin Coconut Oil (VCO) as a value-added product with the potential to increase household income. The program employed socialization activities, presentations, educational video screenings, and hands-on training in VCO production using the fermentation method. Participants included village officials, housewives, and local residents who were actively involved in all stages of the training, including raw material selection, coconut grating, coconut milk extraction, fermentation, oil separation, and final product filtration. The results demonstrated a significant improvement in participants’ understanding and practical skills related to VCO production. Community members were able to independently produce VCO and showed strong enthusiasm for developing coconut-based micro-enterprises. Furthermore, the program increased public awareness of the importance of utilizing local resources as economically valuable products. Therefore, VCO production training can serve as an effective community empowerment strategy to support economic development and improve community welfare through the utilization of local agricultural resources.